The Effects of Task-Based Instruction on Vietnamese EFL Learners’ Speech Production Capacity - Do, Thi Huyen Thanh (Curtin University, 2021)
This study investigates the effects of task-based instruction on EFL learners’ speech production. The study employed an experimental pre-test/post-test design with the participation of 102 Vietnamese EFL learners who were randomly assigned to two task-based instructional groups (input-based task instruction versus combined input-output task-based instruction) and a comparison group. The results indicate that instruction combining input- and output-based tasks was more effective in improving EFL learners’ speech production capacity than the use of input-based instruction alone.